Convergence and fixed point theorems in convex metric spaces : a survey - Chugh, Renu; Malik, Preety (International Journal of Applied Mathematical Research, 2014)
The aim of this paper is to provide a survey of the fixed point theorems, convergence theorems and stability results of iterative schemes that have been studied by many authors in convex metric spaces. This paper should be a useful reference for those persons wishing to become better acquainted with the area. Keywords: Convex Metric Spaces, Fixed Point, Hyperbolic Spaces, Iterative Schemes, Stability.